OPTIMIZATION OF SOME PHYSICAL FACTORS AFFECTING ENZYMATIC DEGRADATION ON PARASERIANTHES FALCATARIA (L.) NIELSEN SAWDUST, CARBOXYMETHYLCELLUSLOSE (CMC) AND INDULIN BY PHANEROCHAETE CHRYSOSPORIUM BURDS. - Martina, Atria
Abstract: <br The optimization of some physical factors affecting enzymatic degradation on Paraserianthes falcataria sawdust, CMC and indulin by Phanerochaete chrysosporium had been carried out. This experiment was held by submerged immobile fermentation method, began with incubation temperature optimization. The culture was incubated in N-limited medium for two weeks at three different temperatures, 25°C, 30°C and 37°C. The optimum temperature was used for next step at pH variation of 4,0, 4,5 and 5,0 and incubation time of 10, 20 and 30 days. The degradation rate was measured by determining glucose, total organic carbon of cellulose and lignin content of the substrate after incubation. The result showed that the optimum condition for cellulose and lignin degradation were as follow: CMC at 30°C, pH 5,0 within 10 days with a rate of 85,99%; sawdust cellulose at 37°C, pH 5,0 within 10 days with a rate of 51,52%; lignin of indulin at 37°C, pH 4,5 within 10 days with a rate of 51,11% and sawdust lignin at 37°C, pH 4,0 within 10 day-incubation with a rate of 72,22%.